T-Cell Receptor–Transduced T Cells: Clinical Experience. Issue 6 (November 2015) - Robbins, Paul F.
Abstract : Abstract: The large number of T-cell epitopes that have been found to be processed and presented on human tumors, now numbering in the hundreds, provides a rich source of targets for therapeutic interventions aimed at inducing durable tumor regression. Vaccination strategies aimed at inducing responses to these antigens have been largely ineffective, and it has been challenging to generate large numbers of T cells with the functional capacity to mediate durable tumor regressions in adoptive immunotherapy strategies in patients who have common epithelial malignancies. The ability to generate T-cell receptors that recognize shared as well as unique antigens expressed in a wide variety of common tumor types that include lung, breast, ovarian, gastrointestinal, urothelial, and genitourinary cancers provides an opportunity to develop widely applicable therapies based on the adoptive transfer of autologous T cells transduced with those receptors.